ANALYSIS OF LABOR COEFFICIENT IN COLUMN STRUCTURE WORK (CASE STUDY OF THE CONSTRUCTION PROJECT OF THE HIGH PROSECUTOR'S OFFICE OF SOUTH KALIMANTAN PROVINCE) - Maharani, Nadiya; Karim, Abdul (CERUCUK, 2025)
Along with the development of the times, the construction of buildings is also increasing rapidly. In a project, planning the budget of a project using the method of analyzing the price of the unit of work is very necessary as a reference. In the analysis of the unit price of work, there is also a labor coefficient planning which aims to measure the efficient use of labor in a construction project and can optimize the use of human resources in a construction project.The data collection method used is using the work sampling method. Work Sampling is a method that can be used to measure productivity. The productivity value of the workforce can be seen from the results of the standard time calculation. Standard time is the time that can be completed by the workforce in completing work under standard conditions.               The results of the research conducted on the South Kalimantan Provincial High Prosecutor's Office Construction project obtained the value of the labor coefficient in the column structure work in the field which was compared with the labor coefficient in the planning column structure work. Between the two analyses there is a clear difference due to the difference in work methods carried out in the field. This results in the value of the labor coefficient in the field tending to be smaller than the value of the planned labor coefficient.Keywords: Coefficient, Labor, Column